State of food security, its determinants and coping strategies among households in Nigeria - Muhammad, Nurudeen Abubakar (2020)
Nigeria, one of the most populous countries in Sub-Saharan Africa, is blessed with both endowments of natural or human resources, having the capacity to be prosperous, providing basic needs for all its citizens. However, she was still ranked among the poor and undernourished nation in the world, registering very high poverty level, signalling the seriousness of the situation that requires attention. Few related studies had been undertaken but mostly covering smaller sample sizes and often faced with challenges such that drawing a general conclusion was largely impossible. It was against this background that an empirical study was conducted in three waves of general households’ surveys for years 2010-11, 2012-13 and 2015-16, examining food security status and its determinants, as well as its coping strategies among insecure households. The first objective covered an overview on the changes of households’ food security using households’ food security index, a food consumption score approach and arc geographic information system (GIS) maps. Data revealed that the state of households’ food security level was largely moderate, and movement from food insecure state to food secured state was very slow as virtually very few households moved from the former to the latter state. The study reported that the southern part of Nigeria was more food secured as compared to the northern segment attributed to the disparity of socio-economic benefits. The second objective examined the impacts of determinants of food security amongst households. Data on fixed effect panel revealed that expenditure on foodstuffs, household size, household size square, alternative job income, land size, access to amenities and gifts had significant positive influences on household food security. The third objective examined the effects of coping strategies options adopted by insecure households. Household assets and remittances indicated some degrees of negative significance with household food insecurity. The findings queried existing policies, projects and programs which were designed to focus on the poor and food insecure households. The study raised issues on some coping mechanisms that were supposedly to affect food insecurity but were silent especially in rural segment of the society, predominantly hosted by the poor. The study recommended for strong and efficient income promotion strategies in attempt at boosting income level of households, and in turn, improving access to food procurement, achievable through government embarking on projects and programmes that provide alternative income to households like in-farm or off-farm related enterprises. There was the need for policies that complement agricultural production through improving farming techniques, new seed varieties, processing and storage facilities. Educating households on the importance of knowledge in uplifting standard of living of people that acquire it attainable through providing increased investment in the educational sector. Educating households on the danger of increasing household size without corresponding food options should also be intensified. The present study presented the key factors affecting household food security, which was expected to proffer solution to the problem of policy summersault and to create a lasting solution in the area of addressing food security issues among households in Nigeria.